(De-)Localising the Climate: The production of uncertain agencies through climate websites - Papazu, Irina; Elling Scheele , Christian (STS Encounters, 2014)
This article introduces a device-centred approach to the concept of climate engagement through a qualitative analysis of two websites: www.klimabevidst.dk and www.mapmyclimate.dk. While klimabevidst.dk represents a down-to-earth take on individual engagement with the climate, providing users with hands-on guides to green home improvements, www.mapmyclimate.dk seeks to increase the user’s awareness of the phenomenon of global climate change by demonstrating how the user’s actions impact the earth’s future. Using conversations with six individuals centred on these green technologies, we investigate how the scaling techniques employed by the websites impact the user’s sense of agency vis-à‐vis the climate. The analysis suggests that scales can indeed be changed or redefined in a way that is conducive to climate engagement.